(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a common non-communicable disease that poses a significant burden to public health. Globally, there were 589 million people living with diabetes in 2024, a figure projected to rise to 853 million by 2050. In Vietnam, the prevalence among adults aged 30–69 is 7.3%, while the prediabetes rate has reached 17.8%. Adherence to non-pharmacological treatment is a key factor in controlling the disease, yet current practices at ward-level health stations remain limited. Objectives: This study aimed to describe the status of adherence to non-pharmacological treatment and analyze several associated factors among patients with type 2 diabetes mellitus at Binh Loi Trung ward Health Center, Ho Chi Minh City in 2026. Methods: A descriptive cross-sectional study was conducted from January to April 2026 on 266 patients with type 2 diabetes aged 18 and older, who were under management at Binh Loi Trung Ward Health Center and capable of communicating in Vietnamese. Data were collected using the IPAQ-SF (physical activity), the SDSCA (dietary/nutrition), a blood glucose testing and periodic follow-up examination scale (Decision No. 5481/QD-BYT), and a questionnaire on knowledge regarding type 2 diabetes. Results: The overall rate of non-pharmacological treatment adherence (3 components) among the participants was only 25.2%. Specifically, adherence to physical activity reached 74.1%, nutrition/dietary adherence reached 39.5%, and blood glucose testing and periodic follow-up examination adherence reached 38.7%. Several factors statistically associated with non-pharmacological treatment adherence included age <60, marital status, duration of disease diagnosis, satisfaction with counseling, and good knowledge about diabetes. Conclusions: Adherence to non-pharmacological treatment among patients with type 2 diabetes at Binh Loi Trung ward Health Center remains low (25.2%). It is necessary to standardize counseling practices, enhance health education communication, conduct periodic follow-up reminders, and provide support to maintain long-term adherence.